Thermoregulatory and biochemical responses of indigenous sheep and goats to naturally saline water under the pastoral system, a study at the Mid-Rift Valley of Ethiopia - Diriba Tulu; Diriba Tulu; Mengistu Urge Letta; Yesihak Yusuf Mummed; Feyisa Hundessa; Dinaol Belina Kitila (Pastoralism, 2025)
Climate change has worsened water salinization and acidification, creating challenges for animal health and productivity. This study assessed the resilience of indigenous sheep and goats that drink naturally saline water from Lake Basaka, focusing on their physiological and biochemical responses as stress indicators under pastoral system conditions. A cross-sectional study was conducted with a random systematic sample of 260 healthy local adult sheep and goats from 50 households for this study. The current finding revealed that physicochemical analysis of Lake Basaka water showed high salinity, with electrical conductivity at 3,992.53 μS/cm and sodium levels at 1,180.69 mg/L, significantly higher than those in freshwater (641.53 μS/cm and 35.28 mg/L, respectively; p < 0.05). The physiological data indicated that goats and sheep drinking saline water had higher rectal temperatures (39.3°C vs. 39.1°C; p < 0.05) and pulse rates (85.1 vs. 83.2 beats/min; p < 0.05) compared to animals drinking freshwater. Hematologic results revealed elevated hemoglobin levels (13.74 g/dL vs. 9.48 g/dL; p < 0.05) and red blood cell counts (11.51 × 106/µL vs. 9.28 × 106/µL; p < 0.05) in animals consuming saline water. Biochemical profiles showed decreased glucose (60.07 mg/dL vs. 71.33 mg/dL; p < 0.05) and cholesterol levels (54.13 mg/dL vs. 64.93 mg/dL; p < 0.05), along with increased urea (75.18 mg/dL vs. 68.96 mg/dL; p < 0.05) and creatinine (3.48 mg/dL vs. 2.68 mg/dL; p < 0.05). Although physiological and blood parameters were higher in the saline water group, most values remained within normal ranges, indicating the animals’ adaptive capacity. However, prolonged exposure to saline water may impact their long-term productivity and health. The study recommends further research on seasonal changes, interspecies resilience, and sustainable water management strategies to enhance livestock resilience and productivity in dryland regions.